Simple and complex gift exchange in the laboratory. - Heijden, Eline C. M. van der; Nelissen, Jan H. M.; Potters, Jan J. M. (Economic Inquiry, 2001)
We examine an experimental gift exchange game in which the players can improve on the unique no-gifts equilibrium by two different types of gift exchange: simple and complex exchange, respectively. Complex exchange gives higher payoffs than simple exchange, but it requires not only mutual trust, like with simple exchange, but also a substantial degree of coordination. We examine whether players are able to conclude simple and complex exchanges and how this is affected by the move and matching structure of the game. We find that the so-called partners treatment is a precondition for the occurrence of complex exchange. (JEL C90, D63, H55) Reprinted by permission of the publisher.